Upaya Meningkatkan Motivasi dan Prestasi Belajar dengan Buku Awe Inspiring Me dalam Konsep Manajemen Diri - Habibaturrohmah Habibaturrohmah; Abu Hasan Agus R (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
Motivation and self-management are very influential in improving achievement. Motivation can function as a driving force that triggers the implementation of things that are done and expected. Self-management also contributes to the formation of a good self in order to design the things to be achieved, so that they are scheduled and neatly arranged, and help the process of maintaining motivation itself. However, the reality that there is high learning motivation and good self-management is still far from student culture in Indonesia, both at the student and student level. This study aims to present the value of motivation and self-management concepts contained in the book awe inspiring me and how the effectiveness of the book awe inspiring me in increasing motivation and good self-management as an alternative to solving the problem of lack of motivation to learn and student achievement. The research method used is descriptive qualitative with a content analysis approach of library research plus field research with observation, interviews and documentation research instruments. The results obtained from the research are that the book awe inspires me is very motivational and presents a very good concept of self-management.